Es mi informe los archivos secretos de la policía de Stroessner - Boccia Paz, Alfredo 1955-; González, Myrian Angélica; Palau Aguilar, Rosa (CDE, Centro de Documentación y Estudios, 1994)
"Compilation of reports from the archive of Stroessner's police, with commentary by the author. Documents instances of torture and reveals the vast spy network that operated during the stronato"--Handbook of Latin American Studies, v. 57.. - http://www.loc.gov/hlas/